Global Efforts to Combat Child Sexual Abuse: An Examination of International Instruments and Their Implications - Ololade Adejoke Olateru-Olagbegi; Akin O. Oluwadayisi (CV. Pustaka Parawali, 2026)
Globally, particularly in Africa, children’s rights have long been relegated to the back, and sometimes, they are being portrayed as non-existent. Many reasons have been attributed to this, which include archaic culture and tradition, illiteracy, poverty, and an inadequate legal framework for the protection of children. Lately, however, a number of laws and instruments have been adopted to guarantee children's rights worldwide. This paper examines the various international and regional instruments that are in place to guarantee the rights of children and protect them against sexual abuse or exploitation. Four levels of legal protection are identified: international, regional, and sub-regional. It is posited that although all the layers of protection identified are important, the most relevant for the daily experience of child victims of sexual abuse. This, however, does not derogate the importance of other instruments; rather, they form the foundation upon which national and state laws are based. The conclusion of this paper is that, despite the various laws put in place for the protection of the rights of children, the incidents of child sexual abuse, sexual exploitation, and child trafficking for sexual exploitation are increasing at an alarming rate globally. This has been attributed to the poor economic situation and high poverty rate ravaging the country. It is hoped that with improved economic conditions, improved quality education, coupled with concerted efforts by governments and CSOs in enforcing these laws, there would be a drastic reduction in the rate of child abuse and child sexual exploitation being experienced in many countries.